2004
DOI: 10.1073/pnas.0406073101
|View full text |Cite
|
Sign up to set email alerts
|

Distinct endothelial phenotypes evoked by arterial waveforms derived from atherosclerosis-susceptible and -resistant regions of human vasculature

Abstract: Atherosclerotic lesion localization to regions of disturbed flow within certain arterial geometries, in humans and experimental animals, suggests an important role for local hemodynamic forces in atherogenesis. To explore how endothelial cells (EC) acquire functional͞dysfunctional phenotypes in response to vascular region-specific flow patterns, we have used an in vitro dynamic flow system to accurately reproduce arterial shear stress waveforms on cultured human EC and have examined the effects on EC gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
509
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(558 citation statements)
references
References 48 publications
29
509
0
10
Order By: Relevance
“…In vivo post-mortem studies have revealed that plaque disruption usually occurs at the shoulders (6,(25)(26)(27), where the cap is often thinnest and most heavily infiltrated with white blood cells including neutrophils and monocytes (28). Inflammatory markers are also differentially expressed in vivo in disturbed flow regions, such as those created by an eccentric stenosis (29,30). It is believed that local hemodynamic factors and mass transport dictate plaque stability and rupture location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo post-mortem studies have revealed that plaque disruption usually occurs at the shoulders (6,(25)(26)(27), where the cap is often thinnest and most heavily infiltrated with white blood cells including neutrophils and monocytes (28). Inflammatory markers are also differentially expressed in vivo in disturbed flow regions, such as those created by an eccentric stenosis (29,30). It is believed that local hemodynamic factors and mass transport dictate plaque stability and rupture location.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α stimulation upregulates the expression of cell adhesion molecules (Figure 2), which are expressed in atheroprone regions and regions presenting plaque (30,38). It thus creates a dysfunctional endothelium, characterized by the expression of pro-inflammatory molecules and other ligands supporting leukocyte adhesion (39).…”
Section: Discussionmentioning
confidence: 99%
“…Certain waveforms in humans have been associated with certain disease susceptibility. 24 This implies the further evaluation of the MOC platform for research into such pathological processes of the human cardiovascular system.…”
Section: Evaluation Of Fluid Dynamicsmentioning
confidence: 99%
“…Computational studies on realistic vascular geometries showed that arterial branches and curvature induce blood flow separation and recirculation, and in these areas ECs experience low and/or oscillating (reciprocating) WSS stimuli (Dai et al 2004;Ene-Iordache and Remuzzi 2012;Sui et al 2015). In vivo and in vitro studies correlated reciprocating WSS waveforms with EC dysfunctions caused mainly by altered cell signaling, increased permeability, and impaired vessel remodeling (Chiu and Chien 2011;Davies et al 2013).…”
Section: Introductionmentioning
confidence: 99%